Obstructive sleep apnea confers lower mortality risk in acute ischemic stroke patients treated with endovascular thrombectomy: National Inpatient Sample analysis 2010–2018. (20th December 2021) - Lapow, Justin M; Dicpinigaitis, Alis J; Pammal, Rajkumar S; Coghill, Griffin A; Rechester, Osher; Feldstein, Eric; Nuoman, Rolla; Maselli, Kristina; Kodi, Shyla; Bauerschmidt, Andrew; Rosenberg, Jon B; Yaghi, Shadi; et al.
Background: Obstructive sleep apnea (OSA) portends increased morbidity and mortality following acute ischemic stroke (AIS). Evaluation of OSA in the setting of AIS treated with endovascular mechanical thrombectomy (MT) has not yet been evaluated in the literature. Methods: The National Inpatient Sample from 2010 to 2018 was utilized to identify adult AIS patients treated with MT. Those with and without OSA were compared for clinical characteristics, complications, and discharge disposition. Multivariable logistic regression analysis and propensity score adjustment (PA) were employed to evaluate independent associations between OSA and clinical outcome. Results: Among 101 093 AIS patients treated with MT, 6412 (6%) had OSA. Those without OSA were older (68.5 vs 65.6 years old, p<0.001), female (50.5% vs 33.5%, p<0.001), and non-caucasian (29.7% vs 23.7%, p<0.001). The OSA group had significantly higher rates of obesity (41.4% vs 10.5%, p<0.001), atrial fibrillation (47.1% vs 42.2%, p=0.001), hypertension (87.4% vs 78.5%, p<0.001), and diabetes mellitus (41.2% vs 26.9%, p<0.001). OSA patients treated with MT demonstrated lower rates of intracranial hemorrhage (19.1% vs 21.8%, p=0.017), treatment of hydrocephalus (0.3% vs 1.1%, p=0.009), and in-hospital mortality (9.7% vs 13.5%, p<0.001). OSA was independently associated with lower rate of in-hospital mortality (aOR 0.76, 95% CI 0.69 to 0.83; p<0.001), intracranial hemorrhage (aOR 0.88, 95% CI 0.83 to 0.95; p<0.001), and hydrocephalus (aOR 0.51, 95% CI 0.37 to 0.71; p<0.001). Results were confirmed by PA. Conclusions: Our findings suggest that MT is a viable and safe treatment option for AIS patients with OSA.